Anthelmintic Baiting of Foxes against Echinococcus multilocularis in Small Public Area, Japan - Uraguchi, Kohji; Irie, Takao; Kouguchi, Hirokazu; Inamori, Azusa; Sashika, Mariko; Shimozuru, Michito; Tsubota, Toshio; Yagi, Kinpei (Emerging infectious diseases, 2022)
We distributed anthelmintic baits on a university campus in Japan inhabited by foxes infected with Echinococcus multilocularis to design an effective baiting protocol for small public areas. High-density baiting can reduce the risk for human exposure to the parasite to near zero. However, monthly baiting is recommended to maintain this effect.